The Roles of H2O/Tetrahydrofuran System in Lignocellulose Valorization - Li, Jianmei; Zhang, Wenyu; Xu, Shuguang; Hu, Changwei (Frontiers in Chemistry, 2020)
Lignocellulosic biomass as a potential alternative to fossil resource for the production of valuable chemicals and fuels has attracted substantial attention, while reducing the recalcitrance of lignocellulosic biomass is still challenging due to the complex and cross-linking structure of biomass. Solvent system plays important roles in the pretreatment of lignocellulose, enabling the transformation of solid biomass to liquid fluid with better mass and heat transfer, as well as in the selective formation of target products. In particular, H2O/tetrahydrofuran (H2O/THF) system has recently been widely applied in lignocellulose valorization, which has been proved to exhibit outstanding efficiency for the conversion of lignocellulose, solubilization of the intermediates and products, and shifting reaction equilibrium, thereby significantly improving the yield and selectivity of target products, as well as the full utilization of lignocellulose. In addition, THF shows low toxicity, and is known as a renewable solvent which can be produced from bio-derived chemicals. Herein, this review concentrates on the advances of H2O/THF system in lignocellulose valorization in recent years. Several aspects relative to the roles of H2O/THF system are discussed as follows: the pretreatment of lignin, conversion of hemicellulose and cellulose components in lignocelluloses, and the promoting formation of valuable chemicals like furfural, 5-hydroxymethyl furfural (HMF), levulinic acid, and so on, as well as the inhibiting role in humins formation. This review might provide useful information for the design of effective solvent system in full utilization of lignocellulosic biomass.